Green Manufacturing Strategy as a Pillar of Sustainable Innovation A SWOT Analysis - Popy Erlinda Febriani (Generate Digital Publishing, 2025)
Objectives: This research aims to examine the role of green manufacturing strategies as a key pillar in driving sustainable innovation in the Industry 4.0 era, focusing on how the integration of green practices can improve competitiveness, operational efficiency, and environmental sustainability in the manufacturing sector. Research Design & Methods: This study uses a SWOT analysis approach to evaluate the strengths, weaknesses, opportunities and threats faced by companies in implementing green manufacturing strategies. This method helps identify internal and external factors that influence the effectiveness of green manufacturing adoption in the context of modern industrial transformation. Findings: The results show that green manufacturing strengthens sustainable innovation through waste reduction, energy efficiency, and resource optimization. The integration of Industry 4.0 technologies such as Manufacturing Execution Systems (MES), Industrial Internet of Things (IIoT), and Additive Manufacturing supports the achievement of sustainability goals while improving product competitiveness in the global market. Implications & Recommendations: Companies need to strengthen cross-functional collaboration, develop internal capacity to absorb green innovations, and invest in Industry 4.0-based technologies to optimize green manufacturing practices. In addition, a comprehensive SWOT analysis is recommended as a strategic tool to design sustainable innovations that are more adaptive to market dynamics and changing environmental regulations. Contribution & Value Added: This research makes theoretical and practical contributions by offering an integrated SWOT-based analytical framework to drive the implementation of green manufacturing as a sustainable innovation strategy. This study also enriches the literature by linking Industry 4.0 dynamics with sustainability practices in modern manufacturing.